Refusal Strategies in Two Harry Potter Movies - Winny Permataningtyas; Thomas Joko Priyo Sembodo (Lexicon, 2018)
This research investigates refusal acts and the strategies used in Harry Potter and the Philosopher’s Stone and Harry Potter and the Chamber of Secrets movies. It aims to identify what types of refusal acts are used by the characters in the movies and how they are expressed throughout the movies. The data were obtained from the two movies. A total of 91 refusals and 12 adjuncts were found in the movies. The results indicate that indirect refusals were more commonly used (65%) than direct refusals (35%). However, the direct strategy negative willingness/ability is the most commonly used (26%), followed by the indirect strategies Attempt to dissuade interlocutor (21%) and Reason/Explanation (18%). The findings seem to suggest that the characters in the Harry Potter movies tend to express their refusals indirectly, especially through persuasion and explanation.